PERTANGGUNGJAWABAN PIDANA TENAGA MEDIS YANG MELAKUKAN KESALAHAN DIAGNOSA TERHADAP PASIEN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2014 TENTANG TENAGA KESEHATAN - Johana Supra Silaban; Zulfikar Jaya Kusuma; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
From a legal standpoint, negligence or error will be related to the nature of illegal acts carried out by people who are capable of being responsible. A person is said to be able to be responsible if he can realize the true meaning of his actions. And an act is categorized as "criminal malpractice" if it fulfills the formulation of criminal offense, that is, the act must be a disgraceful act and the wrong mental attitude in the form of intentions, carelessness or negligence is carried out. When medical personnel make a diagnosis error, the implications are directly felt by the patient. However, medical personnel who make mistakes cannot immediately be held accountable. Because, there are no regulations that bind medical personnel if they make mistakes related to the problem of misdiagnosis. The purpose of writing this thesis is : first, to find out the consequences that occur from a diagnostic error made by medical personnel to the patient, Secondly, to find out the ideal setting of criminal responsibility for medical personnel who make a diagnosis of the patient. This type of research is normative legal research or can be referred to as doctrinal legal research. From the results of the problem research there are two main things which are concluded, first, medical personnel who make a diagnosis of a patient based on Law Number 36 Year 2014 concerning Health Workers cannot immediately be asked for criminal responsibility, because, there is no regulation that binds medical personnel if make mistakes related to the problem of misdiagnosis. Second, in terms of criminal liability based on Law Number 36 of 2014 concerning Health Workers, the regulation does not regulate the criminal liability of hospitals, for any errors or negligence committed by medical personnel. Keywords: Error Diagnosis - Actions against the Law - Implications